Gender-specific prevalence and risk factors of mild cognitive impairment among older adults in Chongming, Shanghai, China - Liu, Yuewen; Yu, Xing; Han, Peipei; Chen, Xiaoyu; Wang, Feng; Lian, Xuan; Li, Jiayu; Li, Ruijin; Wang, Beibei; Xu, Chunliu; Li, Junxue; Zheng, Yaqing; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: This study explores the gender differences in the prevalence of mild cognitive impairment (MCI) and the correlation between multiple influencing factors. Methods: The sample was comprised of 1325 relatively healthy participants aged ≥60 years in a Shanghai community-dwelling (557 males and 768 females). Cognitive function was assessed by Mini-Mental State Examination (MMSE). The Instrumental Activities of Daily Living (IADL) scale was used to assess the activities of daily living. Results: The overall prevalence of MCI was 15.2%, with 10.2% in men and 18.9% in women. In older male subjects, those with higher the Geriatric Depression Scale（GDS） scores [odds ratio (OR) = 1.07, 95% confidence interval (CI) = 1.01–1.14] and hypertension (OR = 2.33, 95% CI = 1.15–4.73) had a higher risk of MCI. female subjects who were illiterate (OR = 2.95, 95% CI = 1.82–4.78), had a farming background (OR = 1.69, 95% CI = 1.05–2.72), and a history of stroke (OR =1.96, 95% CI = 1.07–3.59) had a higher risk of MCI, but this was not true for males. However, Male subjects who never smoked were less likely to have MCI (OR = 0.22, 95% CI = 0.09–0.54). Additionally, the prevalence of MCI was lower in older women with high grip strength (OR = 0.96, 95% CI = 0.92–0.99) and hyperlipidemia (OR = 0.45, 95% CI = 0.22–0.96). Conclusions: The prevalence of MCI was higher in the population of elderly women compared to men. Moreover, it was found that higher GDS scores, smoking, and hypertension increased the prevalence of MCI in men; whereas a history of farming, illiteracy, and stroke increased the prevalence of MCI in women. High grip strength and hyperlipidemia may decrease the prevalence of MCI in women.